2016
DOI: 10.1002/pts.2203
|View full text |Cite
|
Sign up to set email alerts
|

Functional Barrier Performance of a Polyamide-6 Membrane Towards n -Alkanes and 1-Alcohols

Abstract: Polymeric barrier membranes are widely used in the food packaging area. So‐called functional barriers prevent the packed food from contamination of permeants from the environment or from other packaging components. Aim of the study was to determine barrier properties of non‐polar n‐alkanes (n‐pentane up to n‐tetradecane) and polar 1‐alcohols (1‐propanol to 1‐octanol) of a 12 µm biaxially oriented PA6 film at temperatures between 70°C and 100°C. From the experimentally determined lag times, the diffusion coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The experimentally determined D P values for the applied 38 substances are given in Tables S7–S11 and are shown in Figure 9 , where it can be seen that the tested substances show correlations between their molecular volume ( V ) and their diffusion coefficients D P . Similar correlation has been found in previous studies on the same method [ 25 , 26 , 27 ]. The applied substances followed the Arrhenius relationship (Equation 2) from which the activation energies of diffusion were derived for 15 of the 38 applied substances.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The experimentally determined D P values for the applied 38 substances are given in Tables S7–S11 and are shown in Figure 9 , where it can be seen that the tested substances show correlations between their molecular volume ( V ) and their diffusion coefficients D P . Similar correlation has been found in previous studies on the same method [ 25 , 26 , 27 ]. The applied substances followed the Arrhenius relationship (Equation 2) from which the activation energies of diffusion were derived for 15 of the 38 applied substances.…”
Section: Resultssupporting
confidence: 91%
“…Calibration was performed with injections of known amounts of the applied permeants. The diffusion coefficients ( D P ) were determined according to the lag time method [ 25 , 26 , 27 ] (Equation (1)) and the activation energies of diffusion ( E A ) were calculated from the D P at various temperatures according to the Arrhenius Equation (Equation (2)). …”
Section: Methodsmentioning
confidence: 99%
“…The homologous row of polar 1-alcohols follows a similar correlation as for the nonpolar n-alkanes ( Figure 2). The diffusion coefficient for a substance at a certain temperature is therefore mainly a function of its molecular volume V. This is in good agreement with previous studies on films of the same thickness on oriented PA6 [11] and PET [10,12]. The dashed lines in Figure 2 are correlations for both n-alkanes and 1-alcohols at the given temperature.…”
supporting
confidence: 91%
“…The permeated amounts could be predicted before the lag time has not been reached, thereby, being able to evaluate the functional barriers. The barrier properties of polyamide‐6 (PA6) films were studied using the same method …”
Section: Introductionmentioning
confidence: 99%
“…The barrier properties of polyamide-6 (PA6) films were studied using the same method. 12 Auras, Harte, and Selke 13 performed an isothermal sorption experiment coupled with gravimetric analysis to compare the permeability of ethyl acetate and d-limonene for PLA with PET, polystyrene (PS), polypropylene (PP), and LDPE, previously reported. For ethyl acetate, it was found that the lowest and highest permeability were observed in PET and LDPE, respectively.…”
mentioning
confidence: 99%